Modelling pacemaker oscillations in lymphatic muscle cells: lengthened action potentials by two distinct system effects - Edward J. Hancock; Charlie Macaskill; Scott D. Zawieja; Michael J. Davis; Christopher D. Bertram (Royal Society Open Science)
Lymphatic system failures contribute to cardiovascular and various other diseases. A critical function of the lymphatic vascular system is the active pumping of fluid from the interstitium back into the blood circulation by periodic contractions of lymphatic muscle cells (LMCs) in the vessel walls. As in cardiac pacemaking, these periodic contractions can be interpreted as occurring due to linked pacemaker oscillations in the LMC membrane potential (M-clock) and calcium concentration (C-clock). We previously reported a minimal model of synchronized dual-clock-driven oscillations. While this qualitatively replicated the period of oscillations under different conditions, it did not replicate the action potential shape as it varied under those conditions, particularly as regards the extent or lack of a systolic plateau. Here, we modify the model to replicate the plateau behaviour. Using phase-plane analysis we show two qualitatively different dynamical mechanisms that could account for plateau formation, one largely M-clock-driven, the other largely C-clock-driven. The second case occurs with the introduction of a ryanodine receptor; in both cases, we find improved predictions for calcium levels. With enhanced fidelity to the experimental data, the improved model has the potential to help determine opportunities for pharmacological treatment of lymphatic system pumping defects.